PHOTOVOICE IMPLEMENTATION IN TEACHING ENGLISH GUIDING AT ENGLISH STUDY PROGRAM COLLEGE OF FOREIGN LANGUAGE (STIBA) SARASWATI DENPASAR - Putri, Gusti Ayu (LPPM Universitas Pancasakti Tegal, 2018)
Guiding is a branch of oral communication. In oral communication, guiding can be included as productive skill. English guiding is one of the academic lessons in the fourth semester. Being a tour guide is a very important job in tourism part. In many cases, the tour guide is a traveller's first impression of a foreign country. In other cases a tour guide may be responsible for teaching tourists about the culture and sites in a city or town. Improving students? communicative skill is the goal of teaching English guiding, because the student can express themselves and know how to use language well. In the real situation in teaching guide process, lecturer cannot escape from reality. It occurs because there are some problems faced by the lecture and the student. The lecturer cannot make student pay attention; make the students? lack of creativity in making interactive guiding topics, and engagement in whole teaching learning process. This research applied photovoice as a technique to increase the student?s ability in speaking English guiding. Photovoice is suitable technique in teaching speaking skill in English guiding because it gives student chance to communicate with different context and different social by photo as a learning media. This reviews were taken from Beverly Palibroda (2009) Photovoice implementation and Speaking Assessment from Brown Lavinson (2004). This research was conducted by three cycles such as: pre-test, cycle I and cycle II. In composing this research the writer used qualitative descriptive method by classroom action research (CAR).             The result of this research showed that the mean score in pre-test before implementing Photovoice clearly showed that the ability of the subject under study was relatively ? fairly satisfactory ? in the level of mastery of speaking rubric. There were increasing in cycle I after implementing Photovoice technique. The result of the data analysis of the reflection score in cycle I showed increasing the mean score of 7.11 It was higher than the result of pre-test. In the cycle II, which the treatment was more intensive in order of weakness of the students had been known. The result of the data anaysis of reflection or post-test in cycle II that the mean score was 8.18. The different between mean score in cycle I and II was 1.07. It showed that the student?s speaking guiding ability improved after the researcher applied the photovoice thecnique to the students.